The Role of Private Elementary School Principals In Yogyakarta In Implementing Teaching English For Young Learners - Azizah, Dinar Martia (Universitas Sarjanawiyata Tamansiswa, 2025)
Previous research has shown that school principals play a crucial role in supporting the success of English language teaching for young learners (TEYL) within the context of English as a second language (ESL). However, there has been limited research focusing on the role of principals in supporting the success of TEYL in the context of English as a foreign language (EFL). Therefore, the objective of this study is to describe the role of private elementary school principals in Yogyakarta in the implementation of TEYL. This study is a case study conducted in two private elementary schools (ES) in Yogyakarta that have achievements in the field of English language education. The subjects of this study include the school principals, curriculum coordinators, English teachers, and staff members of ES A and B. The research instruments were developed based on the Principals’ Work Manual (Directorate of Educational Personnel Development for Elementary and Secondary Education, 2017) and were used to collect data through interviews and observations. The data analysis technique to be used in this research referred to Miles, Huberman, and Saldana (2014). The activities in data analysis are data condensation, data display, and conclusion drawing/verification. The findings indicate that the role of private elementary school principals in Yogyakarta in supporting TEYL encompasses several aspects. The aspects are curriculum implementation, student development, teacher professional development and involvement of educational staff, provision of infrastructure, fostering a positive academic culture and atmosphere, enhancing parental and community participation, and organizing additional programs aimed at improving the quality of teaching. The implications of this study suggest that school principals hold a strategic position in assisting teachers to optimize TEYL. Further research could explore the development of training programs for principals to support TEYL within the context of EFL. Keywords: principals, private elementary schools, TEYL, EFL